2016
DOI: 10.1002/pip.2844
|View full text |Cite
|
Sign up to set email alerts
|

GaInP/AlGaAs metal‐wrap‐through tandem concentrator solar cells

Abstract: III–V multi-junction solar cells are promising devices for photovoltaic applications under very high concentration levels of sunlight. Shadowing losses of the front side metallisation and ohmic resistance losses in the metal grid limit the practical cell size typically to around 1 cm2 at 1000 suns. The use of a full back-contact architecture, similar to the metal-wrap-through (MWT) technology known in silicon photovoltaics, can help to overcome this limitation. Furthermore, positioning both the positive and ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Modelling has shown that this approach is especially interesting at high concentration and could not only improve the cell efficiency by 3 absolute percent compared to conventional top electrodes, but also increase the total power generation per wafer by ~20% considering the bus bar suppression. Despite its considerable potential, only one prototype has been fabricated for tandem III-V solar cells and showed non-optimal electrical results, in particular because of current leakage and cell architecture 9 . Indeed, the full fabrication method requires to revisit the process flow for solar cells fabrication, and necessitates the development of vias fabrication, including via etching, insulation and metallization.…”
Section: Introductionmentioning
confidence: 99%
“…Modelling has shown that this approach is especially interesting at high concentration and could not only improve the cell efficiency by 3 absolute percent compared to conventional top electrodes, but also increase the total power generation per wafer by ~20% considering the bus bar suppression. Despite its considerable potential, only one prototype has been fabricated for tandem III-V solar cells and showed non-optimal electrical results, in particular because of current leakage and cell architecture 9 . Indeed, the full fabrication method requires to revisit the process flow for solar cells fabrication, and necessitates the development of vias fabrication, including via etching, insulation and metallization.…”
Section: Introductionmentioning
confidence: 99%